IDENTIFICATION OF MUSCULOSKELETAL COMPLAINTS IN SKILLED CONSTRUCTION PERSONNEL USING THE NORDIC BODY MAP METHOD - Nurjannah, Nurjannah (Universitas Sahid, 2023)
Skilled construction workers are one of the most important aspects of development. Repetitive work over a short period of time will result in musculoskeletal complaints. One of the tasks performed by skilled construction workers is stirring and carrying cement to ongoing construction, work is carried out for 8 hours a day manually. Therefore, researchers want to identify musculoskeletal complaints in skilled construction workers using the Nordic body map method. Based on the results of the Nordic body map questionnaire, it is known that the parts that experience pain are stiffness in the lower neck, left and right shoulders, waist, left and right hands, left and right knees, and left and right feet. This musculoskeletal complaint is caused by a work position that is bent and done repeatedly. The proposal given is to change the working position, use transport tools, and stretch before transporting cement.